Diagnostic Dilemma in Rudimentary Horn Pregnancies: Report of the Eight Cases and a Literature Review - Mehmet Sıddık Evsen; Muhammet Erdal Sak; Ali Özler; Hatice Ender Soydinç; Abdulkadir Turgut; Neval Yaman Goruk; Ahmet Yalınkaya (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVE: Although rudimentary horn pregnancies (RHP) are extremely rare, they may be dangerous. The aim of this study is to present our clinical experience on 8 patients with RHP together with a literature review. STUDY DESIGN: Records of patients with RHP that were managed between January 2008 and December 2011 in a tertiary referral hospital in southeast region of Turkey, were retrospectively analyzed. Eight cases with RHP were identified throughout the study period. RESULTS: The mean age of the patients was 23±3.9 years and the mean gestational age was 14.8±4.8 weeks. Rudimentary horn was localized on the left side in 6 of 8 cases (75%). Four (50%) cases hadbeen referred to our department from other hospitals after horn rupture. Two cases had a history of cesarean section due to malpresentation but interestingly without any information about having a Mullerian anomaly. Two of 4 cases with massive intra-abdominal bleeding which had been transferred from other clinics, presented with shock. There was no maternal mortality. CONCLUSION: In obstetrics and gynecology training more attention should be given to unicornuate uterus because of the risk of rudimentary horn pregnancy and risk of rupture.